Social Piety and Patience Toward the Advance of Nature-Loving Students - Hidayat, Ahmad; Azhar, Muhammad; Anis, Muhammad; Purnomo, Halim (International Journal of Islamic Educational Psychology, 2024)
Mapala, or Mahasiswa Pencinta Alam (Nature-Loving Students), is an official student organization in various higher education institutions. Mapala frequently engages in social activities aimed at preserving nature and its contents. This study aim to determine the influence of social piety and patience on flourishing among nature-loving students. Data collection employed non-probability convenience sampling, in which the respondents were selected based on availability. The respondents in this study were 223 active students and members of Mapala organizations across universities in Indonesia. Data analysis was performed using Structural Equation Modeling (SEM) with the Partial Least Squares (PLS) method, utilizing SmartPLS 3.0 M3 software. The study revealed a statistically significant positive relationship between patience and flourishing, as evidenced by a p-value of 0.000 and a t-value of 9.202. In addition, the level of social piety had a positive and substantial impact on flourishing, as proven by a p-value of 0.020 (less than 0.05) and a t-value of 2.337. These results indicate that patience and social piety are key factors contributing to flourishing among Mapala students.